2002
DOI: 10.1021/ja011928+
|View full text |Cite
|
Sign up to set email alerts
|

Hoogsteen-Based Parallel-Stranded Duplexes of DNA. Effect of 8-Amino-purine Derivatives

Abstract: The structure of parallel-stranded duplexes of DNA-containing a mixture of guanines (G) and adenines (A) is studied by means of molecular dynamics (MD) simulation, as well as NMR and circular dichroism (CD) spectroscopy. Results demonstrate that the structure is based on the Hoogsteen motif rather than on the reverse Watson-Crick one. Molecular dynamics coupled to thermodynamic integration (MD/TI) calculations and melting experiments allowed us to determine the effect of 8-amino derivatives of A and G and of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 75 publications
6
47
0
Order By: Relevance
“…At the 3′-end a thiol molecule was added for immobilization onto the gold sensor surface and, depending on the sequence type, it is further modified or not with three 8-aminoadenines (3 A ). They were prepared on an automatic Applied Biosystems 392 DNA synthesizer as described elsewhere (15,16,34,38,39). 5′-5′ Clamps were prepared in three steps.…”
Section: Methodsmentioning
confidence: 99%
“…At the 3′-end a thiol molecule was added for immobilization onto the gold sensor surface and, depending on the sequence type, it is further modified or not with three 8-aminoadenines (3 A ). They were prepared on an automatic Applied Biosystems 392 DNA synthesizer as described elsewhere (15,16,34,38,39). 5′-5′ Clamps were prepared in three steps.…”
Section: Methodsmentioning
confidence: 99%
“…To date, the parallel structures have been mostly investigated by X-ray [156] [157], IR [158], and NMR [159] [160] techniques. Molecular-dynamics simulations showed that sequences containing a similar number of d(AÀT) and d(GÀC) pairs (which are non-isomorphous) arranged in a reverse WatsonÀCrick structure are unstable, while stable structures were found when Hoogsteen pairing was assumed [161]. For unmodified oligonucleotides, the thermal stability of parallel duplexes is significantly lower compared to antiparallel WatsonÀCrick duplexes.…”
Section: For Example the Duplex [All-(s P )-Ps]-da 12 /T 12 Is More mentioning
confidence: 99%
“…8-Aminoadenine [20] and 8-aminoguanine [21] stabilize parallel duplexes [22] and triplexes as well as antiparallel triplexes [23]. 8-Aminoadenine may stabilize parallel duplexes and triplexes because the amino group is positioned to form an extra hydrogen bond with the keto group of the Hoogsteen thymidine (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%